Improving cowpea cereals based cropping systems in the dry savannas of West Africa - Singh, B.B.; Ajeigbe, Hakeem A. (2002)
Most of the farmers in the dry savannas of West Africa 'plant local varieties of cowpea, millet, sorghum, and groundnut in various intercropping systems with little or no purchased inputs. In this system, the cowpea and groundnut yields are low due to shading by cereals and lack of plant protection measures. The cereal yields are low mainly due to lack of fertilizer. Efforts are being made, therefore, to develop a combination of improved varieties and improved cropping systems for higher productivity and profitability with a minimum use of insecticides and fertilizers. We evaluated four cereal-cowpea intercropping row arrangements involving one cereal: one cowpea, one cereal : four cowpea, two cereal : four cowpea intercrops, and sole crops of improved and local varieties of millet, cowpea, and sorghum with selective application of two sprays of insecticides on cowpea only and 100 kg/ha fertilizer (N.P.K. 15: 15: 15) basal and 20 kgN/ha top-dressed to cereals only. The results indicated sole crop improved cowpea to be most profitable followed by the two cereal: four cowpea intercrop system. Farmer participatory evaluation of the improved intercrop system involving two rows of sorghum: four rows of improved cowpea with inputs as indicated above, gave 1 00 to 300% gross economic superiority over the traditional intercropping systems. Smalholder farmers prefer the improved intercropping system over sole crops because it provides them with sufficient sorghum and cowpea for home use and additional cowpea for cash income. Most of the farmers in the dry savannas of West Africa 'plant local varieties of cowpea, millet, sorghum, and groundnut in various intercropping systems with little or no purchased inputs. In this system, the cowpea and groundnut yields are low due to shading by cereals and lack of plant protection measures. The cereal yields are low mainly due to lack of fertilizer. Efforts are being made, therefore, to develop a combination of improved varieties and improved cropping systems for higher productivity and profitability with a minimum use of insecticides and fertilizers. We evaluated four cereal-cowpea intercropping row arrangements involving one cereal: one cowpea, one cereal : four cowpea, two cereal : four cowpea intercrops, and sole crops of improved and local varieties of millet, cowpea, and sorghum with selective application of two sprays of insecticides on cowpea only and 100 kg/ha fertilizer (N.P.K. 15: 15: 15) basal and 20 kgN/ha top-dressed to cereals only. The results indicated sole crop improved cowpea to be most profitable followed by the two cereal: four cowpea intercrop system. Farmer participatory evaluation of the improved intercrop system involving two rows of sorghum: four rows of improved cowpea with inputs as indicated above, gave 1 00 to 300% gross economic superiority over the traditional intercropping systems. Smalholder farmers prefer the improved intercropping system over sole crops because it provides them with sufficient sorghum and cowpea for home use and additional cowpea for cash income.